Effect of microcapsules of chia oil on Ω-3 fatty acids, antioxidant characteristics and oxidative stability of butter - Rahman Ullah (Lipids in Health and Disease, 2020)
Abstract Background Ω-3 fatty acids perform several therapeutic functions in the body, however, their applications are limited due to the inferior oxidative stability. To improve the oxidative stability and release properties of Ω-3 fatty acids, microencapsulation is performed. Butter is a good source of fat-soluble vitamins and antioxidant systems however, it is not a good source of Ω-3 fatty acids. Supplementation of butter with microcapsules of vegetable oils rich in Ω-3 fatty acids is not reported in literature. Methods Microcapsules of chia oil (MCO) were prepared using chitosan as encapsulating material by spray drying at lower temperature. Unsalted butter prepared from cultured cream using Lactococcus lactis ssp. Lactis at 21 °C for 16 Hrs. Cream was churned at 12 °C and microcapsules of chia oil were added to the butter during the working stage at four different concentrations i.e. 2, 4, 6 and 8% (T1, T2, T3 and T4, respectively). Butter without supplementation of MCO were kept as control. Butter samples were stored for 90 days at -10 °C. Butter composition, antioxidant capacity, fatty acid profile, induction period, free fatty acids, peroxide value and sensory evaluation were performed at 0, 45 and 90 days of storage. Results Addition of MCO in butter did not have any effect on standards of identity of butter. Microencapsulation had no effect on fatty acid profile of microcapsules of chia oil. Concentration of alpha-linolenic acid (ALA) in control, T1, T2, T3 and T4 were 0.49, 4.29, 8.41, 13.21 and 17.44%, respectively. Concentration of ALA in fresh and 90 days stored butter samples were 17.44 and 17.11%, respectively. After 90 days of storage, loss of eicosapentaenoic acid (EPA), docosapentaenoic acid (DPA) and docosahexaenoic acid (DHA) were 0.07%, 0.05 and 0.03%, respectively. At 0, 45 and 90 days of storage, 2, 2-Diphenyl-1-picrylhydrazyle (DPPH) free radical scavenging activity of free chia oil was 39.81, 71.22 and 62.18%, respectively. However, microcapsules of chia oil had superior antioxidant activity. DPPH free radical scavenging activity of microcapsules at 0, 45 and 90 days of storage was 36.51, 36.43 and 35.96%, respectively (p > 0.05). Total antioxidant capacity of microcapsules at 0, 45 and 90 days of storage was 70.53, 69.88 and 68.52%, respectively (p > 0.05). It was recorded that induction period of free chia oil and microcapsules was only 2.86 h and 8.55 h. Among the butter samples, control revealed the lowest induction period. While, induction period of experimental samples was not different from each other. Peroxide value and free fatty acids of the butter samples at the end of storage period (90 days) was less than the European Union standards limit (10MeqO2/kg and 0.2%). Sensory characteristics of experimental samples were similar to the control. MCO can be added in butter to improve its functional value. Conclusion Concentration of Ω-3 fatty acids in butter up to 8% can be increased through microcapsules of chia oil with reasonable oxidative stability and no effect on sensory characteristics.